Fostering Adolescent Well-Being through Psychological Capital: A Systematic Review of the HERO Model - Ritika Goyal; Meenakshi Chauhan; Manoj Bajaj (The Bioscan, 2025)
Adolescents’ mental health and well-being have become a central concern in developmental psychology, particularly in the face of rising stressors. Psychological Capital (PsyCap), conceptualized through the HERO model—Hope, Efficacy, Resilience, and Optimism(Luthans et al., 2007) has emerged as a promising protective factor in adult populations. However, its relevance and application to adolescent well-being remain underexplored in a systematic and synthesized manner. This systematic review aims to synthesize empirical studies examining the relationship between PsyCap (or its individual constructs) and well-being among adolescents. Following PRISMA guidelines, relevant articles published between 2012 and 2024 were sourced from PubMed, and Google Scholar. Inclusion criteria were peer-reviewed, English-language, quantitative studies involving adolescents (10–19 years) and employing validated measures of PsyCap and well-being. A total of 30 studies met the eligibility criteria. Results suggest a consistent positive relationship between each HERO component and various dimensions of adolescent well-being, including life satisfaction, emotional health, and psychological flourishing. The review highlights key methodological trends, theoretical underpinnings, and practical implications for school-based interventions and youth mental health policies. Gaps in longitudinal research, measurement consistency, and cultural contexts are also discussed. This review underscores the potential of PsyCap in promoting adolescent resilience and flourishing, warranting deeper cross-cultural and developmental exploration.